Agronomic zinc biofortification of potato (Solanum tuberosum) through soil and foliar zinc sulphate application in Rajasthan - NAGAR, B L; SINGH, JAGDISH; YADAV, D L; VERMA, HANUMAN PRASAD; MEENA, R R (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during winter (rabi) seasons of 2020–21 and 2021–22 at Agricultural Research Station, Kota, Rajasthan to assess agronomical biofortification of potato (Solanum tuberosum L.) through soil and foliar zinc sulphate application The experiment consisted of 7 treatment combination of soil and foliar applications in a randomized block design with 4 replications. The results revealed that the application of ZnSO4 @2.5 kg/ha at the time of planting and foliar application of zinc sulphate @0.2% at 25 and 50 DAP (T7) gave significantly higher total tuber yield, and number of tubers. A significantly higher tuber zinc content was observed under treatment T7, where soil application of ZnSO4 @12.5 kg/ha at planting + 0.2% foliar application of ZnSO4 at 25 and 50 days after planting (DAP) compared to control, indicating more Zn accumulation. The benefit-cost analysis of tuber production under different basal soil application levels and foliar application revealed highest benefit-cost ratio of 2.59 with treatment T7 followed by T6 (2.39) and T3 (2.35). The apparent recovery efficiency and partial factor productivity were also higher with combined application of ZnSO4 through soil as well as foliar application. The experiment highlights the importance of soil and foliar zinc sulphate application for improved tuber yield and zinc fortification in a sustainable and cost-effective manner.